2013
DOI: 10.1186/ar4274
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid fragments enhance the inflammatory and catabolic response in human intervertebral disc cells through modulation of toll-like receptor 2 signalling pathways

Abstract: IntroductionIntervertebral disc (IVD) degeneration is characterized by extracellular matrix breakdown and is considered to be a primary cause of discogenic back pain. Although increases in pro-inflammatory cytokine levels within degenerating discs are associated with discogenic back pain, the mechanisms leading to their overproduction have not yet been elucidated. As fragmentation of matrix components occurs during IVD degeneration, we assessed the potential involvement of hyaluronic acid fragments (fHAs) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 41 publications
1
91
2
Order By: Relevance
“…A possible explanation could involve the growth of nerves capable of signaling pain deep into the annular structures 84 . Another hypothesis involves a class of molecules, called damage-associated molecular patterns (DAMPs), including hyaluronic acid and fibronectin fragments, able to stimulate sterile inflammation of the disc through the action of pro-inflammatory cytokines (IL-1beta, IL-6, and IL-8) and matrix degrading enzymes (MMP-1, MMP-3, and MMP-13) 83 .…”
Section: Type Of Spinal Pain According To Pain Generatormentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation could involve the growth of nerves capable of signaling pain deep into the annular structures 84 . Another hypothesis involves a class of molecules, called damage-associated molecular patterns (DAMPs), including hyaluronic acid and fibronectin fragments, able to stimulate sterile inflammation of the disc through the action of pro-inflammatory cytokines (IL-1beta, IL-6, and IL-8) and matrix degrading enzymes (MMP-1, MMP-3, and MMP-13) 83 .…”
Section: Type Of Spinal Pain According To Pain Generatormentioning
confidence: 99%
“…Another hypothesis involves a class of molecules, called damage-associated molecular patterns (DAMPs), including hyaluronic acid and fibronectin fragments, able to stimulate sterile inflammation of the disc through the action of pro-inflammatory cytokines (IL-1beta, IL-6, and IL-8) and matrix degrading enzymes (MMP-1, MMP-3, and MMP-13) 83 . Also, subclinical anaerobic bacterial infection, encouraged by hypoxic conditions, could have a role in the development of discogenic pain 84 .…”
Section: Type Of Spinal Pain According To Pain Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study found high mobility group B1, a TLR2 ligand, increases with the grade of degeneration in surgical specimens (35). Furthermore, TLR2 activation increases IL-1␤, IL-6, IL-8, matrix metalloproteinase-1 and -13, and COX-2 gene expression and IL-6 protein in a mixed population of NP and AF cells (11,36). These prior studies indicate that TLR2 could play an important role in the increase of inflammatory mediators and catabolic enzymes that contribute to disc degeneration.…”
Section: Tlr2 Regulates Ngf Via Nf-bmentioning
confidence: 99%
“…TLR2 and TLR4 are thought to be the primary TLR subtypes that recognize ECM alarmins, where TLR4 functions as a homodimer and TLR2 functions as a homodimer or heterodimer with TLR1 or -6 (10). TLR activation increases the catabolic proteases matrix metalloproteinase-1 and -13 as well as IL-1␤, IL-6, and IL-8 in disc cells (11,36). Interestingly, in vivo injection of fibronectin fragments into rabbit discs induces degenerative changes (37), and exposure of NP cells to fibronectin fragments decreases proteoglycan synthesis and increases proteoglycan degradation (38).…”
mentioning
confidence: 99%